Evaluasi Kepatuhan Perpajakan Pengadaan Barang dan Jasa Dispendukcapil Kabupaten Malang - Dhea Galuh Nugraheni; Widi Dwi Ernawati; Indra Lukmana Putra (Jurnal Akuntansi Publik Nusantara, 2025)
Reseach evaluates tax compliance in the procurement of goods and services at the Department of Population and Civil Registration of Malang Regency, specifically concerning the calculation, remittance, and reporting of Income Tax Article 22, Article 23, and Value Added Tax (VAT). The research focuses on a local government institution obligated to fulfill tax duties in accordance with prevailing regulations. This applied research employs an exploratory method using interviews, observations, and documentation based on the 2023 procurement budget reports. In general, tax reporting procedures complied with regulations through the DJP Online system, supported by Bank Jatim as the reporting intermediary. However, several discrepancies were identified, such as misclassification of income tax on printed material procurement, inaccurate daily transaction recording, and inconsistencies in payment and remittance dates. Tax remittance occasionally exceeded the ideal post-completion period. Technical issues also occurred during reporting via the Coretax DJP system, particularly delays and data entry errors. Contributes to improving the accuracy of tax administration in local government entities. It is recommended that treasurers exercise greater care in classifying tax objects and strengthen coordination with the Regional Financial and Asset Agency (BKAD) to ensure smooth digital tax reporting. The findings underscore the importance of enhancing human resource capacity and leveraging information technology to support optimal public sector tax compliance.